Cooperação Militar Brasil Suriname: de 1975 a 2014 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The objective of this paper is to analyze military cooperation between Brazil and Suriname, since in the last decades South America has become a fundamental platform for the strategy of international insertion, modernization of national defense and the maturing of regional relations in security and defense issues . The analysis was made from 1975, the year of independence of Suriname and the beginning of its diplomatic relations with Brazil, following the year 2014, which corresponds to the end of the first term of President Dilma Rousseff. scientific articles, news and books on the subject, military cooperation agreements between Brazil and Suriname. A documentary analysis of the main declarations, speeches and positions of the social and political actors of the region to the respect of their perceptions and actions before the military cooperation agreements
Keywords: Cooperação militar; Brasil (País); Suriname (País); Defesa; CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL::RELACOES INTERNACIONAIS, BILATERAIS E MULTILATERAIS